Molecular epidemiological characteristics of osteoarthritis-associated Brucella melitensis in China: evidence from whole-genome sequencing-based analysis - Lei Zhu; Chi Zhang; Chen Liang; Li Peng; Huanyu Yan; Xiuwen Liang; Youjia Xu (BMC, 2024)
Abstract Background Brucellosis, developing complications including arthritis, spondylitis, sacroiliitis, and osteomyelitis, is one of the most common zoonotic diseases in the current world which causes economic losses to the livestock industry and is a great public health concern. Brucella melitensis are the main pathogen of brucellosis epidemics in China, most of which are located in northern China. However, there is limited knowledge about the epidemiology of osteoarthritis-associated brucellosis. This study was aimed to reveal the prevalence of osteoarthritis-associated brucellosis in Inner Mongolia and also to investigate the molecular characteristics of B. melitensis isolates. Methods and results In 2018, the osteoarthritis symptoms of brucellosis in the Brucellosis department of a hospital in Inner Mongolia were investigated. Twenty osteoarthritis-associated B. melitensis strains, isolated from the inpatients in Inner Mongolia during 2013-2017, were subjected to whole genome sequencing. The multilocus sequence type (MLST) and core genome SNP (cgSNP) analysis were conducted to detect molecular epidemiological characteristics. The incidence of brucellosis osteoarthritis symptoms in males (85/120, 70.8%) was significantly higher than that in females (35/120, 29.2%), and the age of patients was concentrated between 41 and 60 years old. In silico analyses indicated ST8 was the prevalent sequence type and the transmission of osteoarthritis-associated B. melitensis among different geographical areas. All strains carry virulence genes, including cgs, lpsA, manCoAg, pgm, pmm, virB4, wbdA and wboA. Conclusion Our study showed the close epidemiologically connection of osteoarthritis-associated B. melitensis strains in northern China. And ST8 was the prevalent sequence type which need our attention.